Anti-inflammatory effect of Chang-An-Shuan on TNBS-induced experimental colitis in rats - Hong Mi; Feng-bin Liu; Hai-wen Li; Jiang-tao Hou; Pei-wu Li (BMC, 2017)
Abstract Background Inflammatory bowel disease (IBD), denominated by Crohn's disease and ulcerative colitis, is often associated with abdominal pain, diarrhea and bloody stool. The standard protocols for treating colitis conditions are not satisfactory; thus, complementary and alternative medicines have been increasingly accepted by IBD sufferers worldwide. In this study, we aimed to elucidate the anti-inflammatory effect of Chang-An-Shuan (CAS), a 6-herb Chinese medicinal formula, on 2, 4, 6-trinitrobenzenesulfonic acid (TNBS)-induced colitis in rats and the underlying mechanisms. Methods Sprague-Dawley rats were administered with rectal gavage of 2.5% TNBS in 50% ethanol for the induction of experimental colitis which is considered as a model for Crohn's disease. Upon the TNBS induction, rats were given CAS at 0.5 g/kg/day or 5 g/kg/day for 10 days. The application of salicylazosulfapyridine (0.5 g/kg/day) was served as a positive reference drug for the colitis condition. The efficacy and mechanistic action of CAS were evaluated by means of histopathological and biochemical approaches such as histological staining, real-time polymerase chain reaction, Western blotting analysis and enzyme-linked immunosorbent assay. Results Oral administration of CAS at 5 g/kg/day, but not 0.5 g/kg/day, significantly ameliorated the severity of TNBS-induced colitis as evidenced by the reduced loss of body weight, alleviated diarrhea and decreased bloody stool. While lowering the disease activity index, the administration of CAS lessened mucosal lesions thus mucosal integrity of the colitis rats was notably improved. Further, the CAS treatment also significantly suppressed the mRNA and protein levels of pro-inflammatory cytokines, namely interleukin-1β and tumor necrosis factor-α while enhancing the level of anti-inflammatory cytokine IL-10 in the TNBS-treated rats. Importantly, the ameliorative effect of CAS was related to an inhibition of the nuclear factor-κB (NF-κB) signaling pathway by downregulating the expression levels of NF-κBp-65, p-38 and p-AKT. Conclusions We suggest that CAS is a potential alternative remedial approach for treating IBD conditions, and the anti-inflammatory effect of CAS is associated with the down-regulation of the NF-κB signaling pathway and the balanced production of pro- and anti-inflammatory cytokines.